2014
DOI: 10.1016/j.pharep.2013.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Enhancement of antinociceptive effect of morphine by antidepressants in diabetic neuropathic pain model

Abstract: Combination therapy, such as classical antidepressants (amitriptyline, moclobemide) with opioids, or agents with noradrenaline reuptake inhibition and μ-opioid receptor activation could be a new target for research into treatment of painful diabetic neuropathy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 42 publications
1
8
0
Order By: Relevance
“…There is also evidence that the antihyperalgesic effect of opioids is improved by the association with some drugs, such as the antidepressants amitriptyline, moclobemide and reboxetine [165] . In line with this idea, new molecules that integrate additional mechanisms to the opioid receptor agonism have been shown efficacy in reducing nociceptive behavior in animal models of DNP, such as the cebranopadol, a nociceptin/orphanin FQ peptide and opioid receptor agonist [166] , and the mu opioid receptor agonist and norepinephrine reuptake inhibitor, tapentadol [162,167] .…”
Section: Opioidsmentioning
confidence: 99%
“…There is also evidence that the antihyperalgesic effect of opioids is improved by the association with some drugs, such as the antidepressants amitriptyline, moclobemide and reboxetine [165] . In line with this idea, new molecules that integrate additional mechanisms to the opioid receptor agonism have been shown efficacy in reducing nociceptive behavior in animal models of DNP, such as the cebranopadol, a nociceptin/orphanin FQ peptide and opioid receptor agonist [166] , and the mu opioid receptor agonist and norepinephrine reuptake inhibitor, tapentadol [162,167] .…”
Section: Opioidsmentioning
confidence: 99%
“…10,[12][13][14][15] Furthermore, other studies demonstrated that pro-inflammatory cytokines released from activated glial cells after repeated Morphine injections participates as between-system mechanism. [16][17][18][19] Morphine tolerance and dependency is a complex physiological response that involves a within-system and a between-system adaptation.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, it is well known that, activation of the NMDA subtype of glutamate receptors, through G protein associated with opioid receptor and intracellular mechanisms such as the subsequent downstream signals (like nitric oxide), and the activation of protein kinas C (PKC) where both NO and PKC are involved in the development of Morphine analgesic tolerance and dependency. 7,[9][10][11] Evidences from previous studies suggested that NMDA receptors are involved in the plasticity that arises from the long-term administration of morphine. [20][21][22][23][24] In the present study pretreatment with Magnesium sulfate (20,40 and 60 mg/kg, ip) 30 min before daily Morphine administration reduced tolerance and dependency of Morphine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…As a group, they inhibit reuptake of norepinephrine and serotonin thereby enhancing descending inhibitory pathways of pain with additional effects on NMDA receptors and sodium channels [81]. The antidepressant effects may be additionally beneficial, particularly in cancer patients, who are more prone to depression; furthermore amitriptyline enhances the antihyperalgesic effects of co-administered morphine [82]. The analgesic dose required is less than the antidepressant dose.…”
Section: Tricyclic Antidepressantsmentioning
confidence: 99%